Teaching Of Reading In The Midst Of Uncertainties: The Narratives Of Elementary Laboratory School Teachers - Adil, Zoraida M. (Shanti Journal, 2022)
Teaching of reaching brought a monumental implication to teaching and learning. This qualitative-narrative research aimed to determine the narratives of Cotabato Foundation College of Science and Technology Elementary Laboratory School. Results showed that teachers were challenged by unresponsive learners, lack of parental support, and lack of reading materials. Meanwhile, they provided their learners with remedial reading activities. They advised that teachers must be passionate and compassionate in handling learners to enhance their reading skills.